Noma (cancrum oris) in the South African context. (4th May 2013) - Feller, L.; Altini, M.; Chandran, R.; Khammissa, R. A. G.; Masipa, J. N.; Mohamed, A.; Lemmer, J.
<x xml:space="preserve">Abstract</x> Noma (cancrum oris) is a destructive necrotising disease affecting orofacial tissues predominantly of malnourished young children. It is characterised by a rapid acute onset which usually starts in the mouth, spreads intra‐orally destroying soft tissue and bone and progresses to perforate the facial skin, causing disfigurement. Polybacterial anaerobic infection is critical too, but is not alone sufficient for the initiation of noma. Cofactors, first and foremost malnutrition, but also systemic viral and bacterial infections are crucial to the development of noma. A patient with necrotising stomatitis or noma must be admitted to hospital for antibiotic treatment, fluid and electrolytes as well as nutritional supplementation and general supportive treatment. The epidemiology of noma in the South African population is unknown, and the clinicopathological features are poorly characterised. Although worldwide there is no evidence that HIV infection is a strong risk factor for noma, HIV infection may play a substantial role in the pathogenesis of noma in South Africa.